Agricultural Lolium perenne seeds as a low-cost biosorbent for Safranine T adsorption from wastewater: Isotherm, kinetic, and thermodynamic studies - Karadeniz, Sabri Can; Isik, Birol; Ugraskan, Volkan; Cakar, Fatih (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
Recently, the negative effects of organic/inorganic pollutants such as dyes and heavy metals on the environment, increasing in direct proportion with increasing industrial developments and urbanization, have become an important problem. Lignocellulosic materials have emerged as promising materials for the treatment of waste-water which is containing pollutants due to their low cost, sustainability, abundance, environmentally friendly nature, and high efficiency. In this study, Lolium perenne seeds were utilized for the adsorptive removal of Safranine T from an aqueous environment for the first time. From the adsorption results, it was determined that the adsorption process was suitable for the Langmuir isotherm (r2 = 0.99). As a result of the adsorption pro-cesses, it was observed that the removal of the Safranine T dye reached up to 91.37%, and the adsorption ca-pacity was calculated as 322.58 mg/g at 25 degrees C and pH approximately equal to 7 according to the Langmuir model. From the kinetic models, it was determined that the adsorption process followed the pseudo-second-order kinetic model. Furthermore, the surface area of adsorbent seeds was calculated as 142.32 m2/g using the Langmuir model. Thermodynamic experiments also stated that the process occurred exothermically (Delta HoA =-6.38 kJ/mol at 25 degrees C) and spontaneously (Delta GoA =-27.57 kJ/mol at 25 degrees C) in nature. The adsorption mechanism was attributed to the electrostatic interactions, 7C-7C, n-7C interactions, and H-bonds between the functional groups of the surface of the adsorbent and dye molecules. This study suggests that Lolium perenne seeds are promising and reusable adsorbents for the treatment of wastewater.
Keywords: Adsorption; Safranine T; Lolium perenne; Isotherms; Kinetics; Thermodynamics; AQUEOUS-SOLUTION; DYE REMOVAL; METHYL-ORANGE; ACID; EQUILIBRIUM; BIOSORPTION; PERFORMANCE; ADSORBENT; BIOCHAR; Geology; Meteorology & Atmospheric Sciences; Water Resources